Prevalence and correlation analysis of lateral discoid Meniscus with degeneration or injury of the Meniscus and articular cartilage in the entire tibiofemoral joint - Chengwei Qin; Yonghua Zhang; Zhe Tian; Yaohua Shang; Pengfei Li (BMC Musculoskeletal Disorders)
Abstract Background The current discussion comprehensively addresses the injury and treatment of discoid lateral meniscus. However, it is important to note that an unfavorable biomechanical environment caused by the discoid lateral meniscus not only leads to self-injury but also has a significant impact on adjacent structures. Therefore, the aim of this study was to investigate the relationship between discoid lateral meniscus and injuries in both the meniscus and cartilage within the total tibiofemoral joint. Methods Patients undergoing knee magnetic resonance imaging examinations at our outpatient clinic were screened, and a total of 278 patients were enrolled in the discoid lateral meniscus group, while 279 patients were enrolled in the non-discoid meniscus group. The type of discoid lateral meniscus was classified according to the Watanabe classification, while meniscal and articular cartilage injuries were classified using the Stoller and Hepple classifications, respectively. The prevalence of discoid lateral meniscus and injuries to the meniscus and articular structures within the tibiofemoral joint in the general population was assessed, along with their relationship. Results The prevalence of discoid lateral meniscus was 8.5%, while the incidence of tibiofemoral joint injury was 10%. Notably, the discoid lateral meniscus group exhibited a significantly higher incidence of tibiofemoral joint injury (P < 0.001). Among these cases, there were 93 patients with type I discoid lateral meniscus and 185 patients with type II discoid lateral meniscus. Specifically, the type I discoid lateral meniscus group showed a significantly higher percentage of lateral meniscus injuries (P < 0.005), whereas the type II discoid lateral meniscus group demonstrated a significantly higher percentage of medial tibiofemoral joint injuries (P < 0.005). Conclusion The lateral discoid meniscus causes knee joint biomechanical abnormalities, increasing the risk of injury and degeneration in the tibiofemoral joint. Type I lateral discoid meniscus is prone to self-tearing and secondary ipsilateral articular cartilage injury. Type II lateral discoid meniscus may remain intact over a wider age range but is associated with a higher risk of injury and degeneration in the medial tibiofemoral joint.